Estado del arte de factores estratégicos en la implementación de una cervecería artesanal. (2021)
This work is developed under the premise and objective of conducting a literature review where strategic factors for the implementation of craft beer producing organizations are identified, with the purpose to have for future opportunities a list of relevant factors and strategies that contribute to the organization. It is also important to bear in mind that these factors are not exclusive to a brewery but are more relevant in an organizational environment focused on the production of craft beer.